First remarks for the edition of Lorenzo Venier's "Zaffetta" (AOQU (Achilles Orlando Quixote Ulysses). Journal on Epic, 2022)
Composed by Lorenzo Venier (1510-1550) in 1531, probably with Pietro Aretino’s complicity, La Zaffetta is a poem in ottava rima, of moral and satirical tone, which tells the gang rape of Angela Zaffetta, a venetian courtesan. This article presents a new philological discussion and an analysis of the text in Seventeenth-Century Venice.
Keywords: Lorenzo venier; Pietro Aretino; Angela Zaffetta; courtesans; Venice; Seventeenth-century Italian Literature